2018
DOI: 10.1016/j.jcin.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Hemodynamics in Patients With Severe Aortic Stenosis and Coronary Artery Disease Undergoing Transcatheter Aortic Valve Replacement

Abstract: ObjectivesIn this study, a systematic analysis was conducted of phasic intracoronary pressure and flow velocity in patients with severe aortic stenosis (AS) and coronary artery disease, undergoing transcatheter aortic valve replacement (TAVR), to determine how AS affects: 1) phasic coronary flow; 2) hyperemic coronary flow; and 3) the most common clinically used indices of coronary stenosis severity, instantaneous wave-free ratio and fractional flow reserve.BackgroundA significant proportion of patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 38 publications
(48 reference statements)
1
85
0
1
Order By: Relevance
“…The feasibility and accuracy of using iFR in patients with severe AS has been demonstrated in several studies. [70][71][72] The data suggest that a lower iFR cut-off (0.82 or 0.83) is better predictive of ischaemia-provoking lesions compared with that validated in patients with no AS. 70 72 This is likely explained by the greater resting blood flow due to the larger myocardial mass and partial microcirculatory vasodilatation which would produce greater transstenotic pressure gradients.…”
Section: Aortic Stenosismentioning
confidence: 88%
See 1 more Smart Citation
“…The feasibility and accuracy of using iFR in patients with severe AS has been demonstrated in several studies. [70][71][72] The data suggest that a lower iFR cut-off (0.82 or 0.83) is better predictive of ischaemia-provoking lesions compared with that validated in patients with no AS. 70 72 This is likely explained by the greater resting blood flow due to the larger myocardial mass and partial microcirculatory vasodilatation which would produce greater transstenotic pressure gradients.…”
Section: Aortic Stenosismentioning
confidence: 88%
“…This was explained by an observed increase in systolic flow following TAVR (thus affecting whole-cycle indices), with no appreciable change in diastolic flow immediately after TAVR and thus no change in iFR. 71 The remainder of the NHPRs have not been assessed in this context. There may be perceivable benefits to diastolic-only rather than whole-cycle indices in this context given the largely variable systolic physiology immediately before and after valve deployment.…”
Section: Special Patient and Lesion Subgroupsmentioning
confidence: 99%
“…Severe aortic stenosis disproportionately impacts the measurement of hyperemic indices in the catheterization lab [94]. Hyperemic indices have been noted to increase significantly following transcatheter aortic valve implantation (TAVI), whereas resting flow (specifically in the wave-free period of diastole) remains unchanged [94]. The improvement in microcirculatory function following TAVI appears to be independent of the severity of concomitant coronary artery disease [94].…”
Section: Functional Assessment Of Coronary Lesions In Special Populatmentioning
confidence: 99%
“…Hyperemic indices have been noted to increase significantly following transcatheter aortic valve implantation (TAVI), whereas resting flow (specifically in the wave-free period of diastole) remains unchanged [94]. The improvement in microcirculatory function following TAVI appears to be independent of the severity of concomitant coronary artery disease [94]. This suggests that, when a patient has both severe AS and CAD, the aortic lesion may be the predominant lesion unless the instantaneous wave-free ratio is ≤0.74.…”
Section: Functional Assessment Of Coronary Lesions In Special Populatmentioning
confidence: 99%
“…41 This is due to the unequal changes on proximal pressure waveforms caused by stenosed aortic valve, the haemodynamic effect of the uncoupling of aortic valve closure from a decrease in left ventricular pressure, and the effect of left ventricular hypertrophy on microvascular function. 42 However, a recent study by Ahmad et al showed iFR values did not change pre-and post-TAVR (p=0.73), whereas FFR decreased significantly post-TAVR compared with pre-TAVR (p=0.001),indicating iFR may be reliable in identifying significant CAD 43.…”
mentioning
confidence: 94%